Pengaruh Lompat Tali (Rope Jump) Terhadap Keseimbangan Dinamis Pada Anak di SDN Losari 153 Surakarta - Yuliani, Rizky Trias, Dwi Kurniawati, SST.FT, M.Kes (2017)
Background : Children at primary school age have the desire to do a great physical activity that required a good dynamic balance to reduce the risk of falls. One method for improving the dynamic balance in children is through jumping rope. Objective : To determine the effect of rope jump on dynamic balance in children in SDN Losari 153 Surakarta. Methode : It is a quasi expremental research of pre-post with control group design. Sample is taken by purposive sampling methode. Sample of the research is 34 individuals. The instrument of this reserch is using balance beam walking test. Effect test used wilcoxon and effect difference test use Mann Whitney. Result of Research : Wilcoxon tes result the group treated with p = 0,002 . The control group with p = 0,206. The result of influence of different test with Mann Whitney test obtained by value p = 0,012. Conclution : There is a rope jump influence on dynamic balance in children in SDN Losari 153 Surakarta.